IDENTIFICATION OF STUDENTS’ MISCONCEPTIONS USING ISOMORPHIC TEST: THE CASE OF NEWTON’S LAW OF MOTION - Fathiah Alatas; Siti Ilhamiah; Ahmad Suryadi (EDUSAINS, 2021)
IDENTIFIKASI MISKONSEPSI SISWA MENGGUNAKAN UJI ISOMORFIK: KASUS HUKUM NEWTON TENTANG GERAKAbstractStudents' misconceptions can lead to learning failure if they are not addressed. In this study, using Google Form, we identify students’ misconceptions using the isomorphic test method on Newton's Law of Motion, especially the principles of dynamics. This study is quantitative research conducted in three junior high schools in South Tangerang. There are 90 participants involved that was selected by purposive sampling method. The research instrument was an isomorphic test in form of multiple choice with nine questions with three indicators namely: analyzing the application of Newton’s I law in daily life; analyzing the correlation between force and mass and the acceleration of a moving object; and analyzing the application of Newton’s III Law in daily life. The results showed that the students were identified as having misconceptions in Newton’s Law concept using isomorphic tests, including misconceptions of inertia and misconceptions of Newton’s Third Law of Motion. One of the misconceptions is that students assume an object will maintain its initial position in motion by applying a new force in the opposite direction. The students' misconceptions found in this study can be used as a reference so that they can be overcome in the learning process.AbstrakMiskonsepsi dapat menyebabkan siswa sulit belajar jika tidak segera diatasi. Dalam penelitian ini, dengan menggunakan Google Form, kami mengidentifikasi miskonsepsi siswa menggunakan instrumen tes isomorfik pada materi Hukum Newton tentang gerak, khususnya pada prinsip-prinsip dinamika. Studi ini merupakan penelitian kuantitatif yang dilaksanakan di tiga SMP di Tangerang Selatan. Terdapat 90 partisipan yang dilibatkan yang dipilih dengan metode purposive sampling. Instrumen penelitian berupa tes isomorfik berupa pilihan ganda dengan sembilan soal dengan tiga indicator yaitu menganalisis penerapan hukum I Newton dalam kehidupan sehari-hari; menganalisis hubungan antara gaya dan massa dengan percepatan suatu benda yang bergerak; dan menganalisis penerapan Hukum 3 Newton dalam kehidupan sehari-hari. Hasil penelitian menunjukkan bahwa siswa teridentifikasi mengalami miskonsepsi pada konsep Hukum Newton. Diantara miskonsepsinya adalah siswa berasumsi bahwa benda akan mempertahankan posisi awalnya dalam gerak dengan memberikan gaya baru dalam arah yang berlawanan. Miskonsepsi siswa yang ditemukan dalam studi ini dapat menjadi referensi sehingga dapat diatasi dalam proses pembelajaran.